PERLAKUAN AKUNTANSI CAPITAL EXPENDITURE DAN REVENUE EXPENDITURE PADA PT. PUTRA KARANGETANG - Kalungan, Trifosa Ryna; Ilat, Ventje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Capital expenditure and revenue expenditure are expenditures that need to be differentiated in the operational activities of an entity of course in fixed assets. Financial Accounting Standar Board Number 16 on fixed assets, a reference in this study. PSAK No. 16 is an accounting standard concerning fixed assets. Within the company, the fixed assets is a part that has a major contribution in the company's expenses. the fixed assets of companies should be able to distinguish between two types of expenses, capital expenditure and revenue expenditure. Object of study are that separate capital expenditure and revenue expenditure together with the accounting treatment on PT. Putra Karangetang. The purpose of this study is to find out how the accounting treatment of capital expenditure and revenue expenditure has been in accordance with PSAK no. 16. Data collection techniques used observation, interview and documentation. The method used is descriptive qualitative. The result of the research shows that the measurement of capital expenditure and revenue expenditure has not been in accordance with PSAK No. 16 (revision 2015), and company policy on the recognition of expenditures related to assets, namely: a). expenses above Rp. 2.500.000 is recognized as capital expenditure whereas b). spending below Rp. 2.5 million is recognized as revenue expenditure.Keywords:Â capital expenditure, revenue expenditure